The Effect of Aplication the Cooperative Learning Model Make a Matchon Students’ Learning Competencies at Junior High School in Solok - medina fadilla; Rahmawati Darussyamsu; Yosi Laila Rahmi; Syamsurizal syamsurizal (Universitas Negeri Padang, 2019)
Research on the problems that exist in Solok 1 Junior High School, student learning competencies are still low. The efforts that can be done are to implement a time learning model that contains scientific literacy. The purpose of this study was to determine the effect of apply the cooperative learning model type make a match on the learning competency of students' in Solok 1 Junior High School. This type of research was experimental research with a randomized control group posttest only design. The population in this study were all class VII Solok 1 Junior High School registered in the 2018/2019. Sampling was done using Purposive Sampling techniques. VIIg as the experimental class and VIIfas the control class. The instruments used were in the form of posttest questions for knowledge competencies, observation sheets for attitude and skills competencies. Based on the results of the study using the t-test it can be concluded that the knowledge competencies of students t count 4,53 > t table 1.67, the attitudes competency t count 2,18> t table 1.67, and the skills competency tcount 5,93 > t table 1.67. it shows that the hypothesis was accepted. So, the application of the cooperative learning model type make a matchcan improve the competency of knowledge, attitudes, and skills of class VII students of Junior high school 1 Solok.